Utilizing Pharmacists to Optimize Medication Management Strategies During the COVID-19 Pandemic. (April 2022) - Burgess, L. Hayley; Cooper, Mandelin K.; Wiggins, Elizabeth H.; Miller, Karla M.; Murray, Edward; Harris, Scott; Kramer, Joan S.
As the COVID-19 pandemic swept through the United States, our heath-system mobilized clinical pharmacy services to address critical clinical medication management needs. Reinforcing recommended medication management strategies for clinical pharmacists was key to successful implementation. Best practice strategies include converting patients from intravenous (IV) to oral medication, transitioning to IV push medication administration, evaluating standard medication administration timing, reviewing metered dose inhaler (MDI) and nebulizer utilization, using alternatives for medications in short supply, reviewing coronavirus disease COVID-19 treatment recommendations, reviewing COVID-19 patient care on interdisciplinary rounds, de-prescribing and de-escalating to eliminate unnecessary medications, and assessing for appropriate venous thromboembolism prophylaxis. These strategies served to help protect medication supply, reduce number of staff entries into patient rooms to conserve personal protective equipment, limit nursing time in patient rooms to reduce COVID-19 exposure risk, and to conserve compounding supplies. Here we present example medication management guidance as used by a large healthcare system during the COVID-19 pandemic.